Gambaran Kadar Kolesterol Pasien Yang Mendapatkan Terapi Bekam - Tri Puspa Rini; Darwin - Karim; Riri - Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Consuming high cholesterol food has risk in increasing blood cholesterol level. The increased of blood cholesterol level is associated with incidence of heart disease. Many traditional treatments that can reduce cholesterol level. One of them is cupping therapy. The research aim to describe the level of cholesterol patient who received cupping therapy. The research was conduct at Rumah sehat AR-Rahmah, Pekanbaru. This descriptive study was involved 36 respondents and was selected by using purposive sampling method. The result showed an average distributions cholesterol levels on client who recieved cupping therapy. Based on the value of central tendency mean cholesterol value before cupping therapy was 200,61 mg/dl and mean of cholesterol value after cupping therapy was 197,94 mg/dl. the result showed cholesterol level on client who received cupping therapy is relatively stable and there was no significant difference. Cupping therapy process requires more time to be able to see the systemic effect of cupping therapy on cholesterol level. Keywords: blood cholesterol, cupping therapy